Study of early cholecystectomy for mild and moderate acute cholecystitis as per Tokyo Guideline - Nandi, Mintu Mohan; Kuiri, Shib Shankar; Sharma, Yash; Kumar, Purushottam; Ghosh, Goutam; Mandal, Nilay (Asian Journal of Medical Sciences, 2018)
Background: According to Tokyo Guidelines, 2007 operative management of acute cholangitis and cholecystitis to be administered earlier with preference of laparoscopic cholecystectomy over conventional open cholecystectomy. Aims and Objectives: This study was done to compare conventional cholecystectomy and laparoscopic cholecystectomy with respect to duration of operation, post operative recovery, analgesic requirement, complications encountered, duration of hospitalization, and patient satisfaction. Materials and Methods: A prospective randomized trial of 50 patients conducted at B.S.M.C.H, Bankura from January 2013 to July 2014, who admitted with a diagnosis of acute calculous cholecystitis, were randomized to undergo open and laparoscopic cholecystectomy with 25 patients in each group. Result: The commonest presenting complaint in both the groups was pain in the right upper quadrant followed by vomiting and dyspepsia. The duration of laparoscopic method was significantly more than open method (median 120min v/s 90min respectively).The duration of pain and analgesic, antibiotic requirement was less in laparoscopic group compared to open group. The intra operative complications were more for the laparoscopic procedure. Wound infection was seen in none of laparoscopic patient but only in 2 patients of open procedure. Two patients of laparoscopic group required conversion to open procedure. The postoperative compliance is better in laparoscopic patients compared to open patients and hospital stay is also significantly less. Conclusion: The laparoscopic procedure was costly compared to open procedure. But this difference was overcome by the other costs incurred in postoperative period of open procedure. The laparoscopic procedure offered better cosmetic compared to open method. Asian Journal of Medical Sciences Vol.9(3) 2018 21-26